2007
DOI: 10.2337/db06-0843
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Turnover of Phosphatidylinositol-4,5-Bisphosphate in Insulin-Secreting Cells Mediated by Ca2+ and the ATP-to-ADP Ratio

Abstract: P hosphatidylinositol 4,5-bisphosphate (PIP 2 ) is a minor membrane component of eukaryotic cells constituting ϳ1% of the phospholipids in the inner leaflet of the plasma membrane. Nevertheless, the phospholipid plays important roles in the regulation of a variety of cell functions. Apart from serving as a precursor for the messenger molecules inositol-1,4,5-trisphosphate (IP 3 ) and diacylglycerol generated on activation of phospholipase C (PLC) (1), and for phosphoinositide 3-kinase-generated phosphatidylino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 49 publications
2
45
0
2
Order By: Relevance
“…Inhibition of PI4K activity not only affected PtdIns(4)P levels, but also abolished the synthesis of PtdIns(4,5)P 2 , in accordance with previous observations with phenylarsine oxide (Thore et al, 2007). When 200 mM LY294002 was added during the ATPinduced increase in the concentration of the phosphoinositides, the PtdIns(4)P levels immediately decreased, whereas those of PtdIns(4,5)P 2 started to decline after a delay of 25±4 seconds (Fig.…”
Section: Single-cell Imaging Of Plasma-membrane Ptdins(4)p Dynamicssupporting
confidence: 75%
See 2 more Smart Citations
“…Inhibition of PI4K activity not only affected PtdIns(4)P levels, but also abolished the synthesis of PtdIns(4,5)P 2 , in accordance with previous observations with phenylarsine oxide (Thore et al, 2007). When 200 mM LY294002 was added during the ATPinduced increase in the concentration of the phosphoinositides, the PtdIns(4)P levels immediately decreased, whereas those of PtdIns(4,5)P 2 started to decline after a delay of 25±4 seconds (Fig.…”
Section: Single-cell Imaging Of Plasma-membrane Ptdins(4)p Dynamicssupporting
confidence: 75%
“…5E). Glucose has previously been found to induce oscillations of the plasma-membrane PtdIns(4,5)P 2 concentration (Tamarina et al, 2005;Thore et al, 2007). Parallel recordings with OSBP PH -CFP and PLCd1 PH -YFP demonstrated that the periodic peaks in the plasma-membrane concentration of PtdIns(4)P coincided with pronounced PtdIns(4,5)P 2 nadirs (Fig.…”
Section: Glucose Induces Ptdins(4)p Oscillations In the Plasma Membranementioning
confidence: 85%
See 1 more Smart Citation
“…Real-time imaging studies in isolated insulinoma cells and intact islets (Thore et al, 2004;Tamarina et al, 2005;Thore et al, 2007) have recently confirmed that glucose stimulates PLC activity secondary to the elevation of [Ca 2+ ] i and that membrane depolarization alone (Gromada et al, 1996;Liu et al, 1996) or increase of [Ca 2+ ] i (Mathias et al, 1985;Best et al, 1987;Biden et al, 1987) In addition to contributing to the generation and shaping of Ca 2+ signals, PLC activation can be anticipated to regulate insulin secretion kinetics via generation of DAG and activation of PKC. Several conventional, novel and atypical PKC isoforms are expressed in islets and insulin-secreting cells (Jones and Persaud, 1998;Warwar et al, 2006).…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 97%
“…1C). Studies in the authors' laboratory have employed TIRF microscopy for measurements of the plasma membrane PtdIns(4,5)P 2 and PtdIns(3,4,5)P 3 concentrations using the PH domains from PLCδ1 and protein kinase B/Akt (16)(17)(18)(19). TIRF microscopy provides better resolution as the optical section is several-fold thinner than in confocal microscopy.…”
Section: Introductionmentioning
confidence: 99%